2004
DOI: 10.1115/1.1924534
|View full text |Cite
|
Sign up to set email alerts
|

Hot Corrosion of Lanthanum Zirconate and Partially Stabilized Zirconia Thermal Barrier Coatings

Abstract: The hot corrosion resistance of lanthanum zirconate and 8wt.% yttria-stabilized zirconia coatings produced by thermal spraying for use as thermal barriers on industrial gas turbines or in aerospace applications was evaluated. The two ceramic oxide coatings were exposed for various periods of time at temperatures up to 1000°C to vanadium- and sulfur-containing compounds, species often produced during the combustion of typical fuels used in these applications. Changes in the coatings were studied using a scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 10 publications
2
30
1
Order By: Relevance
“…It has been reported that lanthanum zirconate TBC was more resistant than YSZ one at the attack of V 2 O 5 at 1000 °C: no spallation and no meaningful changes in microstructure occurred. Otherwise, YSZ TBC failed by cracking and spallation [31]. However, when LZ TBC was attached by sulfates at 900 °C, it was rapidly degraded after a few hours, whereas after 360 h YSZ TBC preserved structural integrity and adhesion to the substrate.…”
Section: To This Purpose Previous Experiments Have Demonstrated That mentioning
confidence: 98%
“…It has been reported that lanthanum zirconate TBC was more resistant than YSZ one at the attack of V 2 O 5 at 1000 °C: no spallation and no meaningful changes in microstructure occurred. Otherwise, YSZ TBC failed by cracking and spallation [31]. However, when LZ TBC was attached by sulfates at 900 °C, it was rapidly degraded after a few hours, whereas after 360 h YSZ TBC preserved structural integrity and adhesion to the substrate.…”
Section: To This Purpose Previous Experiments Have Demonstrated That mentioning
confidence: 98%
“…The most typical corrosive chemicals for TBCs in a gas turbine engine include vanadium compounds (V2O5, NaVO3), sulfur-containing compounds (SO2 and sulfate salts such as Na2SO4, MgSO4), and the mixture of them [73,74]. When the APS deposited LZ based TBC was exposed to the single corrosive chemical at high temperature, it was less damaged by the vanadium compounds (at 1000 o C) but severely attacked by the sulfur-containing compounds (at 900 o C).…”
Section: Hot Corrosion and Cmas Infiltration Damagementioning
confidence: 99%
“…In the vanadia environment, many micro-cracks were generated in the 8YSZ coating, and spallation occurred finally. However, the 8YSZ coating showed an excellent resistance to sulfur-containing compounds [73]. In expecting to improve the corrosive resistance from Na2SO4 and V2O5, the LZ coating was deposited using EB-PVD with the addition of Y2O3 [74].…”
Section: Hot Corrosion and Cmas Infiltration Damagementioning
confidence: 99%
“…The importance of developing coatings with advanced tribological and mechanical properties, and resistance to high-temperature oxidation, is increasing with applications embracing such fields as aeronautics, medicine and automotive industries [1,2]. Most often, in applications, such as machining, casting, or hot-forming, the protective layers are subjected to high-temperature exposure.…”
Section: Introductionmentioning
confidence: 99%